Ethics and Passion in Research Work - Madalińska-Michalak, Joanna (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The paper focuses on the issues of ethics and passion in the work of a scientist. The growing interest in ethical issues within science is linked to the changes we are currently experiencing and the increasing sensitivity to the need to develop and adhere to ethical standards of research. At the heart of the highest standards in scientific work is the accepted way of working and living of scientists involved in the creation of scientific knowledge. The presented analyses direct our attention towards questions about the possible relationship between science and the scientist’s valuable life, about the development of science in the context of changes and challenges currently occurring in science, and finally about the ethos of science and the scientist, for whom passion is one of the sources of freedom and power to construct one’s own identity.